Two new prenylated isoflavones from Hedysarum multijugum. Issue 5 (4th May 2017) - Wang, Wei; Zhao, Yu-Ying; Chen, Hubiao; Zhang, Qing-Ying; Liang, Hong
Abstract: Chemical investigation on the ethyl acetate extract of the roots of Hedysarum multijugum resulted in the isolation of two new prenylated isoflavonoids: 5, 7, 2′-trihydroxy-4′-methoxy-3′-(γ, γ-dimethylallyl) isoflavone (hedysarimisoflavone A, 1 ) and 5, 7, 2′-trihydroxy-4′-methoxy-6, 8-di-(γ, γ-dimethylallyl) isoflavone (hedysarimisoflavone B, 2 ). Their structures were elucidated on the basis of spectroscopic analyses, especially, 1 H and 13 C NMR spectra in conjunction with their 2D experiments, 1 H- 1 H COSY, HMQC, HMBC, and NOESY.